Innovative activities of economic entities: financing, role of banks and problems of interaction under the conditions of marital state - Kryshtal, Halyna; Briukhovetska, Iryna; Khimich, Sviatoslav; Kasadzhyk, Andrii (Management and Entrepreneurship: Trends of Development, 2024)
The purpose of the article is to comprehensively analyze the innovative activity of economic entities in the conditions of martial law, in particular, to study the financial mechanisms of innovation support, the role of banks in ensuring investments and the main problems of interaction between business and financial institutions in extreme conditions. The authors provided recommendations on optimizing the combination of various financial resources, which involves not only attracting investment funds, venture capital, grants and subsidies, but also expanding access to international financial resources and programs. This approach will reduce dependence on own funds and provide additional funding for innovative projects. The theoretical and methodological basis of the research is based on the study of the scientific works of leading scientists in the field of financing innovative development of business entities. In the course of the study, such methods as analysis and synthesis, methods of historical and logical modeling, formalization method, "from abstract to concrete" method, economic interpretation method, method of grouping statistical data, statistical and econometric analysis.  From a practical point of view (research results), these approaches are aimed at creating a comprehensive understanding of innovative activity and its financial support, as well as at identifying optimal strategies for improving the interaction between business entities and financial institutions in the conditions of martial law. The authors considered the main problems of innovative development of business entities in Ukraine in the conditions of martial law and proposed the introduction by the government of a set of financing tools.JEL Classification: М21, М29